Treat-to-target strategies for the management of familial Mediterranean Fever in children - Ehlers, Lisa; Rolfes, Elisabeth; Lieber, Mareike; Müller, Dominik; Lainka, Elke; Gohar, Faekah; Klaus, Günter; Girschick, Hermann; Hörstermann, Jana; Kümmerle-Deschner, Jasmin; Brunner, Jürgen; Palm-Beden, Katharina; et al. (Pediatric rheumatology, 2023)
Background: The objective of this initiative was to develop a treat-to-target (T2T) approach for the management of patients with Familial Mediterranean Fever (FMF), including the definition of a complex treatment target, and establish strategies that improve patient care and long-term outcome. Methods: An initial set of statements as well as a flow chart visualising the proposed concept was developed. To adapt the preliminary statements to the current state of knowledge, a systematic literature search was performed and the modified statements were subject to a Delphi approach. To ensure the applicability of the statements in daily practice, an online survey was conducted among paediatric rheumatologists in Germany. In addition, data from the national AID-NET registry were analysed with respect to therapeutic response. Results: This T2T initiative yielded a total of 26 statements guiding FMF management with respect to diagnosis, treatment targets, treatment strategies and monitoring. The online survey identified cut-off values for inflammatory markers indicating treatment intensification and appropriate measures in case of colchicine intolerance or non-adherence. The analysis of data derived from the national AID-NET showed that colchicine therapy was successfully terminated in 61% of patients (27 out of 44) with heterozygous MEFV mutations. Multidimensional treatment targets incorporating objective and subjective reported outcome measures were developed. These provide the basis for stratifying patients into the following treatment paths: continue colchicine, persisting attacks / inflammation, colchicine intolerance, persisting arthritis, colchicine reduction and adjustment/reduction of biologics. Conclusions: The proposed consensus treatment plan for the management of FMF incorporates multidimensional targets allowing transparent treatment decisions, which will promote personalised disease management and increase adherence to therapy.
Veröffentlicht: 26. September 2023
Gesehen am 15.11.2023